2022
DOI: 10.1007/s12519-022-00653-y
|View full text |Cite
|
Sign up to set email alerts
|

Early recombinant human growth hormone treatment improves mental development and alleviates deterioration of motor function in infants and young children with Prader–Willi syndrome

Abstract: Background Recombinant human growth hormone (rhGH) therapy has shown to improve height and body composition in children with Prader–Willi syndrome (PWS), the evidence of early rhGH treatment on motor and mental development is still accumulating. This study explored the time effect on psychomotor development, anthropometric indexes, and safety for infants and young children with PWS. Methods A phase 3, single-arm, multicenter, self-controlled study was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…In addition, PWS patients exhibited comprehensive developmental delays, including 100% of patients experiencing motor developmental delay and 82.8% of patients aged over 2 years having language developmental delay. Our findings were consistent with previous studies, 31,34,37 showing a correlation between language developmental delay and genotypes, with higher rates in the deletion type than the non-deletion type. Driscoll et al also found motor developmental delay in 90%-100% of PWS children.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, PWS patients exhibited comprehensive developmental delays, including 100% of patients experiencing motor developmental delay and 82.8% of patients aged over 2 years having language developmental delay. Our findings were consistent with previous studies, 31,34,37 showing a correlation between language developmental delay and genotypes, with higher rates in the deletion type than the non-deletion type. Driscoll et al also found motor developmental delay in 90%-100% of PWS children.…”
Section: Discussionsupporting
confidence: 93%
“…They received rhGH treatment after being diagnosed with PWS at the Department of Endocrinology, Children’s Hospital of Fudan University. The inclusion and exclusion criteria were described in the previous paper [ 4 ]. Participants in the non-rhGH treatment group were diagnosed with PWS, who never used rhGH treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Most children with PWS have growth hormone (GH) deficiency, which can be identified through real-time monitoring of daily spontaneous GH release and associated stimulation tests [ 3 ]. Studies have shown that rhGH therapy can improve linear growth, body composition, physical strength, agility, and mental development in children with PWS [ 4 , 5 ]. This treatment should be accompanied by dietary, environmental, and lifestyle interventions for genetically-confirmed PWS patients [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are 3 main types of PWS, including paternal deletion (65-75%), maternal uniparental disomy (mUPD) (20 -30%), and imprinting defects (1-3%). 1 PWS displays significant clinical variability with age, ranging from hypotonia and sucking weakness during infancy to hyperphagia, morbid obesity, hypogonadism, and growth retardation [ 1 4 ].…”
Section: Introductionmentioning
confidence: 99%